Combined evaluation of a panel of protein and miRNA serum-exosome biomarkers for pancreatic cancer diagnosis increases sensitivity and specificity - Madhavan, Bindhu K.; Yue, Shijing; Galli, Uwe; Rana, Sanyukta; Gross, Wolfgang; Giese, Nathalia; Büchler, Markus W.; Zöller, Margot (International journal of cancer, 2015)
Late diagnosis contributes to pancreatic cancer (PaCa) dismal prognosis, urging for reliable, early detection. Serum-exosome protein and/or miRNA markers might be suitable candidates, which we controlled for patients with PaCa. Protein markers were selected according to expression in exosomes of PaCa cell line culture supernatants, but not healthy donors' serum-exosomes. miRNA was selected according to abundant recovery in microarrays of patients with PaCa, but not healthy donors' serum-exosomes and exosome-depleted serum. According to these preselections, serum-exosomes were tested by flow cytometry for the PaCa-initiating cell (PaCIC) markers CD44v6, Tspan8, EpCAM, MET and CD104. Serum-exosomes and exosome-depleted serum was tested for miR-1246, miR-4644, miR-3976 and miR-4306 recovery by qRT-PCR. The majority (95%) of patients with PaCa (131) and patients with nonPa-malignancies reacted with a panel of anti-CD44v6, -Tspan8, -EpCAM and -CD104. Serum-exosomes of healthy donors' and patients with nonmalignant diseases were not reactive. Recovery was tumor grading and staging independent including early stages. The selected miR-1246, miR-4644, miR-3976 and miR-4306 were significantly upregulated in 83% of PaCa serum-exosomes, but rarely in control groups. These miRNA were also elevated in exosome-depleted serum of patients with PaCa, but at a low level. Concomitant evaluation of PaCIC and miRNA serum-exosome marker panels significantly improved sensitivity (1.00, CI: 0.95-1) with a specificity of 0.80 (CI: 0.67-0.90) for PaCa versus all others groups and of 0.93 (CI: 0.81-0.98) excluding nonPa-malignancies. Thus, the concomitant evaluation of PaCIC and PaCa-related miRNA marker panels awaits retrospective analyses of larger cohorts, as it should allow for a highly sensitive, minimally-invasive PaCa diagnostics.